Physical Training Status Determines Oxidative Stress and Redox Changes in Response to an Acute Aerobic Exercise - Farnaz Seifi-skishahr; Arsalan Damirchi; Manoochehr Farjaminezhad; Parvin Babaei (Biochemistry Research International)
Objective. To assess the influence of different physical training status on exercise-induced oxidative stress and changes in cellular redox state. Methods. Thirty male subjects participated in this study and were assigned as well-trained (WT), moderately trained (MT), and untrained (UT) groups. The levels of cortisol, creatine kinase, plasma reduced glutathione to oxidized glutathione (GSH/GSSG), cysteine/cystine (Cys/CySS), and GSH/GSSG ratio in red blood cells (RBCs) were measured immediately and 10 and 30 min after exercise. Results. Following the exercise, plasma GSH/GSSG (p=0.001) and Cys/CySS (p=0.005) were significantly reduced in all groups. Reduction in plasma GSH/GSSG ratio in all groups induced a transient shift in redox balance towards a more oxidizing environment without difference between groups (p=0.860), while RBCs GSH/GSSG showed significant reduction (p=0.003) and elevation (p=0.007) in UT and MT groups, respectively. The highest level of RBCs GSH/GSSG ratio was recorded in MT group, and the lowest one was recorded in the WT group. Conclusion. Long term regular exercise training with moderate intensity shifts redox balance towards more reducing environment, versus intensive exercise training leads to more oxidizing environment and consequently development of related diseases.